PERCEPTION OF YOUTH TOWARDS DIGITAL MARKETING WITH REFERENCE TO PRODUCT CHOOSING BEHAVIOUR - Basu, Sourav (The journal of contemporary issues in business and government, 2022)
In Digital marketing is now acknowledged as one of the most effective strategies for breaking through the noise and having one-on-one conversations with customers. The fact that digital marketing is getting increasingly more individualized is what has led to this recognition. As a consequence, with the trend toward direct, one-to-one marketing, emphasis is being placed more and more on the usage of digital media as a means of effectively reaching consumers. The present study has been carried out to find out the youths’ perception towards digital marketing, to find out whether advertisements demotivate customers and to study whether there is any necessity of digital marketing for promoting new product. For this purpose the researcher has selected a sample of 100 youth with the age ranging from 18-30yrs by following random sampling method. A self structured questionnaire has been used for collecting data from the selected sample. Collected data are analyzed by applying percentage system and Chi Square test. Findings of the study indicate that most of the youth have a positive attitude towards Digital Marketing.